(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background: Tumoral angiogenesis is essential for the growth and spread of breast cancer cells. Objective:To evaluate angiogenesis by measuring microvessel density (MVD) with CD34 and its maturity with smooth muscle actin (SMA) immunohistochemistry and to study invasion of basement membrane by tumor cells using type IV collagen. Methods:In the present study microvascular quantification was undertaken on 52 cases of breast carcinoma and 5 cases of benign breast lesions after immunohistochemical staining of tumor vessel, using CD34 antibody and SMA antibody. Microvessel quantification was performed at x400 magnification in the three most vascular areas of the tumors (hot spots). Results:The difference in MVD between benign and malignant cases is significant (P= 0.001). MVD is significantly correlated with L.N. involvement (P=0.004) and lymphovascular permeation (P=0.001), no statistical significant correlation between MVD and age of patient (P=0.656), tumor size (P=0.052), tumor grade (P=0.324). Conclusion:Measurements of angiogenesis may have clinical utility in the evaluation of breast cancer, particularly for estimation of metastatic risk. A high MVD may be a poor prognostic marker of breast carcinoma and a target for antiangiogenic therapy. Key words: Angiogenesis, CD34, SMA, Collagen IV, breast carcinoma.